2022
DOI: 10.3390/ijms23158148
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine Inhibits Skeletal Muscle Differentiation by Blocking Autophagic Flux

Abstract: Tetrandrine is well known to act as a calcium channel blocker. It is a potential candidate for a tumor chemotherapy drug without toxicity. Tetrandrine inhibits cancer cell proliferation and induces cell death through apoptosis and autophagy. As cancer patients usually experience complications with sarcopenia or muscle injury, we thus assessed the effects of tetrandrine on skeletal muscle cells. We report in this study that a low dose of tetrandrine (less than 5 μM) does not affect the proliferation of C2C12 my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…A positive role for autophagy in myoblast differentiation is supported by our results showing that blocking autophagy in C2C12 myoblasts impaired their expression of muscle-specific genes and their fusion into multinucleated myotubes. Our finding that autophagy plays a positive role in myoblast differentiation was consistent with earlier studies using different approaches or different myoblast models [ 24 , 25 , 26 , 27 , 28 , 29 ]. However, the conclusion that autophagy aids myoblast differentiation seems to contradict the observation that inducing autophagy with the mTOR inhibitor rapamycin inhibited myoblast differentiation in C2C12 cells [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A positive role for autophagy in myoblast differentiation is supported by our results showing that blocking autophagy in C2C12 myoblasts impaired their expression of muscle-specific genes and their fusion into multinucleated myotubes. Our finding that autophagy plays a positive role in myoblast differentiation was consistent with earlier studies using different approaches or different myoblast models [ 24 , 25 , 26 , 27 , 28 , 29 ]. However, the conclusion that autophagy aids myoblast differentiation seems to contradict the observation that inducing autophagy with the mTOR inhibitor rapamycin inhibited myoblast differentiation in C2C12 cells [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…This process includes packaging the target objects in the phagophores derived from the endoplasmic reticulum [ 20 ]; the expansion and sealing of the phagophores with various proteins, including different Atg isoforms [ 21 ]; the establishment of autophagosomes; and the fusion of autophagosomes with lysosomes to form autolysosomes, where the target material for recycling is degraded by lysosomal hydrolases. Autophagy has been linked to muscle regeneration following injury [ 12 ], muscle aging [ 22 ], muscle atrophy [ 23 ], and myoblast differentiation [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main neuroprotective mechanism involves regulating Ca 2+ and K + channels, maintaining intracellular calcium homeostasis, and reducing neuronal and glial cell damage caused by Ca 2+ overload [ 23 ]. In addition, it can regulate central neurotransmitter transport and metabolism, inhibit neuroinflammation, improve vascular endothelial dysfunction, decrease oxidative stress, and regulate autophagy [ 24 , 25 , 26 ]. It has a highly comprehensive neuroprotective effect and is a potential neuroprotective agent.…”
Section: Isoquinoline Alkaloids With Neuroprotective Effectsmentioning
confidence: 99%
“…In agreement with previous studies, Bryant et al observed that MAPK/ERK inhibition can block mitochondrial fission, leading to increased mitochondrial fusion (Bryant et al, 2019). Mitochondrial remodeling is critical for skeletal muscle differentiation and myofiber type transformation (Li et al, 2022). Thus, the cascade phosphorylation process MAPK/ERK plays a critical role in regulating myofiber conversion.…”
Section: Introductionmentioning
confidence: 99%